OsRAMOSA2 Shapes Panicle Architecture through Regulating Pedicel Length - Lu, Huan; Dai, Zhengyan; Li, Ling; Wang, Jiang; Miao, Xuexia; Shi, Zhenying (Frontiers in Plant Science, 2017)
The panicle architecture of rice is an important characteristic that influences reproductive success and yield. It is largely determined by the number and length of the primary and secondary branches. The number of panicle branches is defined by the inflorescence meristem state between determinacy and indeterminacy; for example, the maize ramosa2 (ra2) mutant has more branches in its tassel through loss of spikelet determinacy. Some genes and factors influencing the number of primary and secondary branches have been studied, but little is known about the molecular mechanism underlying pedicel development, which also influences panicle architecture. We report here that rice OsRAMOSA2 (OsRA2) gene modifies panicle architecture through regulating pedicel length. Ectopic expression of OsRA2 resulted in a shortened pedicel while inhibition of OsRA2 through RNA interference produced elongated pedicel. In addition, OsRA2 influenced seed morphology. The OsRA2 protein localized to the nucleus and showed transcriptional activation in yeast; in accordance with its function in pedicel development, OsRA2 mRNA was enriched in the anlagen of axillary meristems, such as primary and secondary branch meristems and the spikelet meristems of young panicles. This indicates a conserved role of OsRA2 for shaping the initial steps of inflorescence architecture. Genetic analysis revealed that OsRA2 may control panicle architecture using the same pathway as that of the axillary meristem gene LAX1 (LAX PANICLE1). Moreover, OsRA2 acted downstream of RCN2 in regulating pedicel and branch lengths, but upstream of RCN2 for control of the number of secondary branches, indicating that branch number and length development in the panicle were respectively regulated using parallel pathway. Functional conservation between OsRA2 and AtLOB, and the conservation and diversification of RA2 in maize and rice are also discussed.